Menggunakan Metode Algoritm Silver Meal dan Algoritm Wagner Within Dengan Demand Dynamic Inventory Dalam Pengendalian Persediaan Bahan Kegiatan Purchase Order - Hermanto Hermanto (Jurnal Syntax Transformation, 2022)
Inventory is a resource that is saved and used to meet current and future needs. Less optimal inventory control policies used by the company often result in an overstock of raw materials as indicated by the value of Days of Inventory (DOI). Factors that affect the DOI value from forecasting needs, the amount of safety stock, remaining inventory and uncertainties originating from suppliers. To be able to minimize the DOI value, in determining the number of material orders or Purchase Orders addressed to the supplier, these factors must be considered so that the inventory is still in a safe number so that there is no excess supply of raw materials which can affect product quality because of the long storage period. too long can reduce the quality of these raw materials. PT. Rofa food Indonesia is a company engaged in the frozen food concept snack industry. To support the smooth production process which in turn will affect the smooth fulfillment of consumer demand, PT. Rofa Food Indonesia always strives to ensure the availability of ingredients as much as possible to avoid material shortages so that they can always meet the target service levels that have been determined by the company through the PPIC (Production Planner Inventory Control) division.